Inhibition of NF-κB activation and MMP-9 secretion by plasma of human volunteers after ingestion of maritime pine bark extract (Pycnogenol) - Ďuračková Zdeňka; Liptáková Anna; Sumegová Katarína; Muchová Jana; Chovanová Zuzana; Grimm Tanja; Högger Petra (BMC, 2006)
Abstract French maritime pine bark extract (Pycnogenol®) displays a variety of anti-inflammatory effects in vivo. Aim of this study was to determine whether human plasma after oral intake of Pycnogenol contains sufficient concentrations of active principles to inhibit key mediators of inflammation. Blood samples from seven healthy volunteers were obtained before and after five days administration of 200 mg Pycnogenol per day. Plasma samples statistically significantly inhibited matrix metalloproteinase 9 (MMP-9) release from human monocytes and NF-κB activation. Thus, we provide evidence that bioavailable active principles of Pycnogenol exert anti-inflammatory effects by inhibition of proinflammatory gene expression which is consistent with documented clinical observations. We suggest that our ex vivo method is suitable to substantiate molecular pharmacological mechanisms of complex plant extracts in a more focussed and rational way compared to in vitro studies by taking into account the processes of absorption and metabolism.